Global Initiative for Chronic Obstructive Lung Disease 2023 Report: GOLD Executive Summary. Issue 4 (3rd April 2023) - Agustí, Alvar; Celli, Bartolome R.; Criner, Gerard J.; Halpin, David; Anzueto, Antonio; Barnes, Peter; Bourbeau, Jean; Han, MeiLan K.; Martinez, Fernando J.; Montes de Oca, Maria; Mortimer, Kevin; Papi, Alberto; et al.
Executive summary of the Global Strategy for Prevention, Diagnosis and Management of COPD 2023: the latest evidence-based strategy document from the Global Initiative for Chronic Obstructive Lung Disease (GOLD ) https://bit.ly/3KCaTGe